Strain generated in the TMJ with class II malocclusions, treated with extraction of premolars and orthodontics: analysis with the finite element method - Sandra Patricia Castaño-Duque; Alejandra Hoyos-Daza; Angela María Vargas-Romero; Luis Eduardo Luna-Ángel (Universidad de Antioquia, 2021)
Introduction: premolar extraction is an alternative for the treatment of class II malocclusion. A change in biomechanics can generate alterations in the Temporomandibular Joint (TMJ), which produces greater dental wear and the appearance of joint dysfunctions. The objective was to assess the effort concentration in the TMJ by means of finite element analysis in class II malocclusions treated with premolar extraction and orthodontics. Method: two 3D simulation models each with bone structures of the 2 jaws, complete dentition and disc in the TMJ. One corresponds to the patient without recurrence (WR) treated with extraction of first premolars and orthodontics, where class I dental stability is maintained. The other model with recurrence (R) treated with extraction of first premolars and orthodontics, increased overjet and overbite and canine class II; the load was applied to the mandibular ramus. Results: loads of 900N triplicated on all structures compared to 300N in both models. However, there were considerable differences between the left and right glenoid cavities in the WR model, at 300N of 19.9 MPa and 900N at 59.3 MPa. Most tensions of the disc occur in the lateral part. Conclusions: due to the asymmetry in the TMJ structures, the stresses and stress concentration differ between the right and left sides in the two models.